1996
DOI: 10.1902/jop.1996.67.5.478
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Periodontal Treatment on Periodontal Bacteria on the Oral Mucous Membranes

Abstract: The aim of this study was to investigate the effect of conventional periodontal treatment on the prevalence of Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, and Prevotella intermedia on oral mucous membranes in patients with periodontitis. Fifteen patients were selected with moderate to severe periodontitis (mean age: 39.8 years, range: 26 to 58). From each patient the 4 deepest sites with bleeding on probing were selected for clinical and microbiological evaluation. At baseline, 6 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 43 publications
7
90
0
2
Order By: Relevance
“…It is not yet clear whether those two species are able to maintain themselves in the absence of a gingival crevice. Previous studies done by microbial culture have reported that A. actinomycetemcomitans and P. gingivalis disappear from the mouth when all teeth are removed (7,8). The negative results for the edentulous subject are interesting in that respect.…”
Section: Fig 3 Three-dimensional Reconstructions Of Two Cells From mentioning
confidence: 84%
“…It is not yet clear whether those two species are able to maintain themselves in the absence of a gingival crevice. Previous studies done by microbial culture have reported that A. actinomycetemcomitans and P. gingivalis disappear from the mouth when all teeth are removed (7,8). The negative results for the edentulous subject are interesting in that respect.…”
Section: Fig 3 Three-dimensional Reconstructions Of Two Cells From mentioning
confidence: 84%
“…On the other side, the irrelevant host response adds to the pathogenesis of the disease. Accumulating data demonstrate that till now there is no unified strategy for the therapy of periodontal inflammations [3][4][5][6][7]. In spite of the numerous publications on the etiology and pathogenesis of periodontal infections, no common diagnostic markers characterizing the response to treatment exist [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…12 Several studies have shown that the periodon topathogens can colonise other intraoral niches such as tongue dorsum, tonsils, saliva and other mucous membranes in addition to the periodontal pockets. 13,14 Intraoral translocation of periodon topathogens from one niche to another has been proven. 15,16 After root surface debridement, the subgingival microfl ora can re-establish from these niches.…”
mentioning
confidence: 99%